Educational disparities in partnership formation and dissolution in Finland (1990–2019) - Andersson Linus; Jalovaara Marika (IUSSP, 2025)
As marriage declines and divorce increases, partnership trends and household composition become increasingly determined by trends in the formation and dissolution of non-marital cohabiting unions. Marika Jalovaara and Linus Andersson show that in Finland, the decline in marriage is not offset by an equivalent increase in cohabitation, and educational disparities in the prevalence of unions have increased somewhat from already-high levels in 1990. These patterns are remarkably similar for men and women.